The functions of code switching in an English language classroom - Eva Fachriyah (Universitas Syiah Kuala, 2017)
The aims of this research is to gain a deep understanding and to knowing the use of code-switching that have done by students and lecturers in interaction when teaching learning in English class. Specifically or as sub-focus in this research was aimed to determine the functions for the use of code switching that is used by both of the speaker and hearer that in this case the interaction between lecturer and students when learning takes place. This research was conducted at the campus of the State Islamic Institute